Manipulating Eryptosis of Human Red Blood Cells: A Novel Antimalarial Strategy? - Boulet, Coralie; Doerig, Christian D.; Carvalho, Teresa G. (Frontiers in Cellular and Infection Microbiology, 2018)
Malaria is a major global health burden, affecting over 200 million people worldwide. Resistance against all currently available antimalarial drugs is a growing threat, and represents a major and long-standing obstacle to malaria eradication. Like many intracellular pathogens, Plasmodium parasites manipulate host cell signaling pathways, in particular programmed cell death pathways. Interference with apoptotic pathways by malaria parasites is documented in the mosquito and human liver stages of infection, but little is known about this phenomenon in the erythrocytic stages. Although mature erythrocytes have lost all organelles, they display a form of programmed cell death termed eryptosis. Numerous features of eryptosis resemble those of nucleated cell apoptosis, including surface exposure of phosphatidylserine, cell shrinkage and membrane ruffling. Upon invasion, Plasmodium parasites induce significant stress to the host erythrocyte, while delaying the onset of eryptosis. Many eryptotic inducers appear to have a beneficial effect on the course of malaria infection in murine models, but major gaps remain in our understanding of the underlying molecular mechanisms. All currently available antimalarial drugs have parasite-encoded targets, which facilitates the emergence of resistance through selection of mutations that prevent drug-target binding. Identifying host cell factors that play a key role in parasite survival will provide new perspectives for host-directed anti-malarial chemotherapy. This review focuses on the interrelationship between Plasmodium falciparum and the eryptosis of its host erythrocyte. We summarize the current knowledge in this area, highlight the different schools of thoughts and existing gaps in knowledge, and discuss future perspectives for host-directed therapies in the context of antimalarial drug discovery.